EXPERT SYSTEM TO DIAGNOSE COW DISEASE USING WEBSITE-BASED DEMPSTER-SHAFER ALGORITHM - Mufa’at Hadi Rosid; Muhamad Fuat Asnawi; Nur Hasanah (Nacreva Publisher, 2023)
Cows are one of the livestock whose existence can meet various kinds of human needs because they are the main producer of animal protein such as meat or milk. However, there are problems that cause failure in running a cattle farm. One of the problems is the health factor of the cattle which is disturbed due to a disease. Limited knowledge and livestock health workers become an obstacle for cattle breeders in analyzing the possibility of disease affecting cattle based on the symptoms that appear. For this reason, an expert system was built that can diagnose cow disease based on a website which can later be an alternative when someone has limited access to experts to diagnose the disease he is suffering from. The dempster-shafer algorithm was chosen because it is able to provide certainty in performing diagnostic calculations. From the results of this study, an expert system for diagnosing cattle disease has been developed using the PHP programming language which can implement the algorithm and can run well, as evidenced by passing the testing phase using the black box test method and also successfully passing the accuracy test with experts. with a percentage of 86.67%.